2022
DOI: 10.14689/enad.30.10
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Theory and Practice: An Examination Based on Pre-Service Teachers' Beliefs

Abstract: The purpose of this study is to conduct an examination based on pre-service teachers' beliefs about the theoretical content of teacher education programmes. The research was carried out with a basic qualitative research design. The study group of the research was determined with the criterion sampling method, which is one of the purposive sampling methods. The study group of the research consisted of 134 pre-service teachers studying in three different programmes in their eighth semester. Analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Therefore, relevant literature emphazises that there is a need to focus on how theoretical knowledge is taught. In fact, Bayrak-Özmutlu (2022), in her article examining the views of preservice teachers on what can be done about the integration of theory and practice, states that the problem of context and trust should be overcome in the teaching of theoretical knowledge. Teaching methods that can overcome these problems in teaching theoretical knowledge can enable preservice teachers to have more elaborated, detailed, and accessible schemas.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Therefore, relevant literature emphazises that there is a need to focus on how theoretical knowledge is taught. In fact, Bayrak-Özmutlu (2022), in her article examining the views of preservice teachers on what can be done about the integration of theory and practice, states that the problem of context and trust should be overcome in the teaching of theoretical knowledge. Teaching methods that can overcome these problems in teaching theoretical knowledge can enable preservice teachers to have more elaborated, detailed, and accessible schemas.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…When we examine the literature focusing on teacher education (Bayrak Özmutlu, 2022;Darling-Hammond, 2000;Darling-Hammond et al, 2017;Korthagen et al, 2006), it is indicated that there are problems in linking theory and practice in university-based teacher education programs. Pre-service teachers' acquisition of field experience is among the prominent proposals for solving this problem.…”
Section: Introductionmentioning
confidence: 99%